2008
DOI: 10.1080/07373930802307324
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Moisture Desorption Isotherms and Thermodynamic Properties of Fermented Tea Dhool (Camellia sinensis var. assamica)

Abstract: The desorption isotherms of fermented tea dhool were determined at 50, 55, 60, and 70 C by using static gravimetric method of saturated salt solutions within the water activity range of 0.05-0.81. Results indicated that the equilibrium moisture contents were decreased with the increase in temperature. A modified Oswin model was well fitted with the experimental data. Desorption isotherm curves obtained were type II sygmoidal. Thermodynamic properties like net isosteric heat of sorption and differential entropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This behavior is due to the presence of strongly bound water molecules to the food at lower moisture levels by the existence of polar groups on the surface of the product. Similar behavior was observed for fermented tea dhool (Botheju et al . 2008).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…This behavior is due to the presence of strongly bound water molecules to the food at lower moisture levels by the existence of polar groups on the surface of the product. Similar behavior was observed for fermented tea dhool (Botheju et al . 2008).…”
Section: Resultssupporting
confidence: 85%
“…Studies have shown that critical moisture content exists in foods in which water molecules are bound strongly to the surface of the monolayer. This moisture content corresponds to the monolayer moisture content ( M m ) and is considered as the optimal moisture content to prevent the alteration of the product quality (Botheju et al . 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous researches have been carried out on the thermodynamics of water vapor sorption in agricultural products, such as fruits and vegetables (McMinn and Magee, 2003;Moreira et al, 2008), seeds and nuts (Taitano et al, 2012;Xing et al, 2012), milk products (Thanuja and Ravindra, 2014), cereal (Martín-Santos et al, 2012), herbal leaves (Dalgic et al, 2012), and fermented tea dhool (Botheju et al, 2008). However, to the best of our knowledge, little information is available about the sorption behavior and thermodynamic properties for marine products, in general, or for P. vannamei, in specific.…”
mentioning
confidence: 99%